1980
DOI: 10.1093/jaoac/63.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Thin Layer Chromatography Reflectometric Determination of Benzoic and Sorbic Acids in Fruit Beverages

Abstract: A procedure is proposed for the quantitative determination of both benzoic and sorbic acids in fruit beverages. This method is carried out by direct ultraviolet spectrophotometric measurements in silica chromatoplates after development with chloroform-methanol-water (65+35+7) and makes use of an internal standard. Applied to samples spiked with benzoic and sorbic acids, this technique gives accurate and reliable results with good recoveries. The sensitivity (about 1 ppm) is particularly convenient for trace le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The relative recoveries of the analytes are given in Table and varied between 90 and 113%, which indicated that the real matrixes in our present context had little effect on HS-LPME. In comparison with the AOAC official methods , and those previously published, the protocol demonstrated a satisfactory reliability, accuracy and repeatability for the determination of BA and SA in soft drinks with complex matrixes. The chromatogram obtained by GC−MS of seawater sample spiked with the target compounds at the concentration level of 50.0 μg L −1 of each analyte after the developed method is shown in Figure .…”
Section: Resultsmentioning
confidence: 77%
“…The relative recoveries of the analytes are given in Table and varied between 90 and 113%, which indicated that the real matrixes in our present context had little effect on HS-LPME. In comparison with the AOAC official methods , and those previously published, the protocol demonstrated a satisfactory reliability, accuracy and repeatability for the determination of BA and SA in soft drinks with complex matrixes. The chromatogram obtained by GC−MS of seawater sample spiked with the target compounds at the concentration level of 50.0 μg L −1 of each analyte after the developed method is shown in Figure .…”
Section: Resultsmentioning
confidence: 77%
“…These parameters are based on sensory properties such as flavor, color, aroma, taste and texture. The quality parameters that are based on quantitative properties such as percentage of sugar, protein, peroxides, free fatty acids, enzymes can be determined via several analytical techniques such as Thin layer chromatography (TLC) , high‐performance liquid chromatography (HPLC) , micellar electrokinetic chromatography , gas chromatography (GC) , and electrochemical techniques . The application of electrochemical techniques in food analysis is promising .…”
Section: Introductionmentioning
confidence: 74%
“…For this reason, the development of appropriate and inexpensive methods to determine BA is of great importance for food safety . To date, thin layer chromatography (TLC) , high‐performance liquid chromatography (HPLC) , micellar electro kinetic chromatography (MEKC) and gas chromatography (GC) have been developed for BA determination. In this study, an electrochemical measurement approach was developed to determine BA in food.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, sodium benzoate is classified as “generally recognized as safe.” It is permitted to use in food materials up to a maximum level of 0.1% . Although, it has been neglected as a catalyst for a long time and less number of reactions carried by using it as catalyst . Therefore, the study of sodium benzoate as environmentally benign catalyst appears to be very reasonable.…”
Section: Introductionmentioning
confidence: 99%